2011
DOI: 10.5897/ajb10.1494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arbuscular mycorrhizal inoculation on nutrient uptake, growth and productivity of cowpea (Vigna unguiculata) varieties

Abstract: The objective of the present study is to find out the effect of Arbuscular mycorrhiza (AM) fungal inoculation on growth, productivity and nutrient uptake in two cowpea (Vigna unguiculata) varieties. The AM inoculated plants out performed than non-inoculated plants (control) in terms of growth, productivity parameters and nutrient uptake. AM fungal inoculation had a significant effect on productivity of cowpea attributed to growth, plant height, number of nodules, mycorrhizal dependency and number of flowers pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
7
11
1
Order By: Relevance
“…number of leaves, leaf length, leaf surface area, stem girth and number of shoots respectively. The present study also confirm the findings that the inoculation of Rhizobium, rock phosphate and Vesicular Arbuscular Mycorrhizae (VAM) significantly increased the growth parameters and growth yield of Burgundy (Macroptilum bracteatum) under "P" deficient soil [17]. The endophytic fungi significantly increased shoot growth, chlorophyll contents, and plant biomass and leaf area of pepper plant as compared to fungal-free plants [16].…”
Section: Resultssupporting
confidence: 87%
“…number of leaves, leaf length, leaf surface area, stem girth and number of shoots respectively. The present study also confirm the findings that the inoculation of Rhizobium, rock phosphate and Vesicular Arbuscular Mycorrhizae (VAM) significantly increased the growth parameters and growth yield of Burgundy (Macroptilum bracteatum) under "P" deficient soil [17]. The endophytic fungi significantly increased shoot growth, chlorophyll contents, and plant biomass and leaf area of pepper plant as compared to fungal-free plants [16].…”
Section: Resultssupporting
confidence: 87%
“…2). These results were for the most part in line with the results of preceding studies, which observed a high response of cowpea to AM fungal colonization and their positive contribution to growth improvement (Yaseen, Burni, & Hussain, 2011;Saidou, Singh, Abaidoo, Iwuafor, & Sanginga, 2012). Previously, Mosse (1986) classified cowpea into 'mycotrophic plants', which was greatly responsive to mycorrhizal colonization.…”
Section: Resultssupporting
confidence: 81%
“…Some recently reports indicate that requirements for nutrients especially phosphorus might affect plant response to mycorrhizal infection (Mosse, 1986;Tawaraya, 2003;Wang, Zhao, & Bücking, 2016). Yaseen, Burni, & Hussain (2011) found that differences in growth response of several genotypes of cowpea to AM related to P supply.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…to the formation of a shorter mycorrhizal root system (Jacobsen, Smith, & Smith, 2002), relying on the fungal mycelium for nutrient uptake (Smith, 2000). In fact, there was a significant enhancement in shoot nutrient content (Table 2), particularly N and P, which has also been described in other studies with inoculated cowpea (Boby, Balakrishna, & Bagyaraj, 2008;Oruru et al, 2018;Sanginga, Lyasse, & Singh, 2000;Yaseen, Burni, & Hussain, 2011 and establishment increases the opportunity of seedlings to achieve a positive C and nutrient balance, which is crucial, especially under stress conditions (de Albuquerque & de Carvalho, 2003). Further studies are, therefore, needed to improve this limitation on the germination of cowpea seeds coated with AM fungi.…”
Section: Consequently Plants Adjust Belowground C Allocation Contribsupporting
confidence: 56%